Resilient Alaska Native Coastal Communities: Integrated Social-ecological Monitoring and Assessment Supporting Adaptation Decisions. Project narrative. - Bronen, Robin; Chapin, Terry; Cochran, Patricia (Alaska Institute for Justice, 2015)
Introduction to the Problem: A rapidly changing climate in the Arctic is dramatically impacting the health and well-being of Alaska Native communities. Erosion and repeated extreme weather events damage infrastructure, including health clinics and water and sewage treatment facilities. Saline intrusion and thawing permafrost impact access to potable water. In the most extreme cases, accelerating rates of erosion are life-threatening and are causing Alaska Native communities to choose to relocate their entire community. Rationale: This research strives to increase the adaptive capacity of Alaska Native communities experiencing the impacts of climate-induced environmental change on their health and wellbeing. Community engagement and empowerment are critical to any process aiming to improve the adaptive capacity of Alaska Native communities. By developing new and building upon existing trust relationships, learning from, and co-producing knowledge with communities, we seek to develop adaptation strategies to protect their health and well-being, and to articulate their needs to organizations that might be able to provide technical or financial assistance. Brief Summary of Work: 1. Design a community-based social-ecological monitoring and assessment methodology that will be used and implemented by Alaska Native communities to enable them to perform their own monitoring. Methodology development will be a cooperative effort led by Alaska Native communities and involving university researchers, government representatives, such as the US Army Corps of Engineers, and non-governmental organizations such as the Alaska Institute for Justice, Alaska Native Science Commission and the Alaska Native Tribal Health Consortium; 2. Train local community representatives to implement this methodology in their community and to perform trial data collection throughout the grant period and use these data to improve the methodology; 3. Document the collaborative relationship between these communities, university researchers, non-governmental organizations and government agencies throughout the grant period; 4. Compare and assess the possible differences in implementation of the social-ecological monitoring and assessment methodology between the five communities; and 5. Disseminate the methodology. Project Title: Resilient Alaska Native Coastal Communities: Integrated Social-ecological Monitoring and Assessment Supporting Adaptation Decisions. Name of Competition: Climate and Societal Interactions: Supporting Resilient Coastal Communities and Ecosystems in a Changing Climate: Understanding climate-related human health risks within the coastal environment. The Alaska Institute for Justice, Alaska Native Science Commission and University of Alaska seek $299,870 for a two-year project. Additional grant partners include the Alaska Native Tribal Health Consortium and the University of Victoria. Works Relevance to Competition & NOAA’s Next Generation Strategic Plan: This interdisciplinary project seeks to foster adaptation in Alaska Native communities by designing a community-based social-ecological monitoring and assessment methodology so that these communities can better assess their vulnerabilities to a changing climate and make informed adaptation decisions. The goals of this research project fit squarely within the parameters of the NOAA Supporting Resilient Communities and Ecosystems in a Changing Climate grant program, and NOAA’s Next-Generation Strategic Plan because this research is interdisciplinary, innovative and designed to collaborate with Alaska Native coastal communities so that they can maintain or improve their health and vitality over time by anticipating and adapting to change.